ICT Enabled Solutions to Challenges - Issues of Integrated Sustainable Tourism & EcoTourism in VIKSIT Madhya Pradesh of VIKSITBharat - A Review of Potential. - Manoj Kr. Singh,; Ashwini Kr. Singh, (AG Volumes, 2026)
The term "Viksit Bharat" translates to "Developed India," and the year 2047 is chosenstrategically as it marks 100 years since India gained its independence. The core idea is to leverage the momentum gained over the past decades and propel India into a league of developed nations, ensuring a high quality of life for all its citizens. As per declaration this movement has been defined with four pillars of the system - The Poor (Garib), The Youth (Yuva), The Women Empowerment (Mahila Sashaktikaran) and The Farmer (Annadata).Madhya Pradesh being a state of India has a lead role in this ongoing movement. It aims to increase the state's gross domestic product (GSDP) from the current ₹15.03 lakh crore to ₹250 lakh crore (US$2 trillion) by 2047. In the course of development in country and state, ICT has become a strong support system that changes the way information and communication are delivered. It has created endless opportunities where citizens can see more than what is happening in surroundings and regulators, policy formulators, administrators, developers & managers can be involved in their process like never before as the time limit chosen is very less. So far we have achieved 4.19 trillion dollar GDP from the year 1947 (during last 78 Years) & targeted to achieve 30-40 trillion dollar GDP in upcoming year 2047 (during upcoming 22 Years only). The only visible way out is achieving it to proceed with high end low cost ICT based decentralized technologies.The essence of development is relationships; it is people (The Yuva - Youth, The Garid - Poor, The Mahila Shakti - Women and The Annadata - Farmer). An environment full of laughter, questions, and feelings best described as happiness cannot be created in a closed room with the help of a screen or a gadget. ICT is not here to make this disappear; ICT is here to expand on it. In this way, with the incorporation of technology into the development process of economic system, we can achieve a balance that develops overall growth and socio-economic well-being. After all, vikas (development) isn’t a mere data-processing activity but a living process, which makes the future of technology and humanity intertwined.This potential review reveals that there is an urgent need to strengthen the system of sustainable tourism & ecotourism by incorporating more cost effective - technology oriented automated services to minimize the operational cost of service providers and efficiency in delivery of it to tourists.More detailed studies should be carried out on continuous basis and results may be shown in public domain. However, a deeper comprehensive studies (evaluation & research studies) by incorporating the sustainability aspects is the urgent need of the sector to carried out for customers’ satisfaction and stakeholders’ perspective. Besides this economics and scale of business to be organized in a better way to make tourism & eco-tourism more sustainable and effective. It also recommends the option of effective & economic customization for tourists and sites should be improved upon to optimize the satisfaction and sustainability.